1 Peter A Critical and Exegetical Commentary: Volume 2: Chapters 3-5 - Horrell, David G. 1963-; Williams, Travis B. 1980- (London Bloomsbury Publishing Plc, 2023)
Cover -- Title -- Copyright -- Contents to Volume II -- General Editors Preface -- Preface -- Maps -- Abbreviations -- Second Major Section of the Letter-Body (2.11-4.11) (continued) -- Instructions to Wives and (More Briefly) to Husbands (3.1-7) -- Summary Instructions to All, and Supporting Scriptural Quotation (3.8-12) -- Suffering for Doing Good, and Being Ready to Give an Account (3.13-17) -- Christ's Suffering, Proclamation to the Imprisoned Spirits, and Vindication (3.18-22) -- Excursus: Preaching to the Spirits in Prison -- Exhortation to Keep Away from Sin and a Past Way of Life, for Judgment Will Come (4.1-6) -- Instructions on Life within the Christian Community (4.7-11) -- Third Major Section of the Letter-Body (4.12-5.11) -- Sharing the Sufferings of Christ and Glorifying God 'as a Christian' (4.12-19) -- Instruction to Elders and to the Whole Community (5.1-5) -- Depending on God and Resisting the Devil (5.6-11) -- Letter Closing and Final Greetings (5.12-14) -- Bibliography.
Description based on publisher supplied metadata and other sources
Keywords: Bible.-Peter, 1st-Commentaries; Electronic books; Kommentar